Ocean acidification trends and carbonate system dynamics across the North Atlantic subpolar gyre water masses during 2009–2019 - D. Curbelo-Hernández; F. F. Pérez; M. González-Dávila; S. V. Gladyshev; A. G. González; D. González-Santana; A. Velo; A. Sokov; J. M. Santana-Casiano (Biogeosciences)
The CO2–carbonate system dynamics in the North Atlantic subpolar gyre (NASPG) were evaluated between 2009 and 2019. Data were collected aboard eight summer cruises through the Climate and Ocean: Variability, Predictability and Change (CLIVAR) 59.5° N section. The ocean acidification (OA) patterns and the reduction in the saturation state of calcite (ΩCa) and aragonite (ΩArag) in response to the increasing anthropogenic CO2 (Cant) were assessed within the Irminger, Iceland, and Rockall basins during a poorly assessed decade in which the physical patterns reversed in comparison with previous well-known periods. The observed cooling, freshening, and enhanced ventilation increased the interannual rate of accumulation of Cant in the interior ocean by 50 %–86 % and the OA rates by close to 10 %. The OA trends were 0.0013–0.0032 units yr−1 in the Irminger and Iceland basins and 0.0006–0.0024 units yr−1 in the Rockall Trough, causing a decline in ΩCa and ΩArag of 0.004–0.021 and 0.003–0.0013 units yr−1, respectively. The Cant-driven rise in total inorganic carbon (CT) was the main driver of the OA (contributed by 53 %–68 % in upper layers and > 82 % toward the interior ocean) and the reduction in ΩCa and ΩArag (> 64 %). The transient decrease in temperature, salinity, and AT collectively counteracts the CT-driven acidification by 45 %–85 % in the upper layers and in the shallow Rockall Trough and by < 10 % in the interior ocean. The present investigation reports the acceleration of the OA within the NASPG and expands knowledge about the future state of the ocean.